MODELS OF THE GAS GENERATOR OF THE HYDROGEN STORAGE AND SUPPLY SYSTEM FOR IMPLEMENTATION OF ITS CONTROL OPTIONY - Abramov, Yu.; Kryvtsova, V.; Mikhailyuk, A. (Municipal economy of cities. Series: «Economy science», 2025)
It is shown that two multiplicative components can be used as a model of the transfer function of the gas generator of the hydrogen storage and supply system, one of which describes inertial processes, and the second characterizes the delay process. An algorithm for determining the equivalent time constant of the gas generator is presented and it is shown that its value is 1.5 times different from the similar value obtained when implementing the algorithm for approximating the amplitude-frequency characteristic of the gas generator. Such an algorithm involves obtaining the ratio for the values of the derivatives of the Hurwitz polynomials of two transfer functions. It is noted that the use of time methods for determining the parameters of the gas generator of the hydrogen storage and supply system when implementing its control option is focused on the application of the transition function of this gas generator. When determining the transition function of the gas generator using the dynamic parameter obtained when approximating its amplitude-frequency characteristic, a methodological error may occur, the value of which reaches 60.0%. It is shown that the use of the algorithm for determining the equivalent time constant of the gas generator of the hydrogen storage and supply system provides the determination of its transition function with a methodological error, the value of which does not exceed 13.2%. When introducing a correction in the structure of the transition function of the gas generator, the value of the methodological error can be reduced to 5.1%. The example shows that depending on the method for determining the time parameter of the gas generator during its control, the value of the methodological error can vary. When using the method for determining the time parameter of the gas generator, which is based on determining the time of reaching a priori a given pressure value in the cavity of this gas generator, the value of the methodological error does not exceed 0.4%.